PENERAPAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN TEMATIK TERPADU DI KELAS II SEKOLAH DASAR (STUDI LITERATUR) - Mayori, Ersa; Taufik, Taufina (Universitas Negeri Padang, 2022)
This research aims to describe the application of the scientific approach in integrated thematic learning in elementary schools. This research is motivated because there are still many mistakes in implementing integrated thematic learning in elementary schools. This research uses a literature study method (library research) through a literature review to strengthen the analysis of the various sources used. This research begins with formulating a research problem followed by analyzing the relevant research results. Data collection in this literature study was carried out using non-tests, namely by searching electronic journals through reputable journals, books, theses, and online journals that are relevant to the application of the scientific approach. The keywords used for journal search are the Scientific Approach, Integrated Thematic. The results obtained from the research will be analyzed by the author using the content analysis method. From the results of the research analysis of 15 relevant journals, it shows that the scientific approach is effectively applied in integrated thematic learning in elementary schools.